Cooperating of rate of exchange is with indexes of balance of payments and international investment position of country: theoretical and methodological context - Голуб, Роксолана Ростиславівна (Technology audit and production reserves, 2015)
It was established that approach to the exchange rate analysis based on a country’s balance of payments estimation (hereinafter BoP) could be considered as an aggregating macro-level approach absorbing the majority of fundamental factors of the exchange rate dynamics. In the analyzed context important current tasks are substantiated: to find out interrelations between exchange rates and balance of payments figures and international investment position of the country; outline theoretical and methodological basis of analysis of the national currency unit revaluation and devaluation factors. It is proved that all conclusions derived from the analysis of external sector accounts are based both on the absence of official and unofficial restrictions on international and internal operations and on the fact that market participants freely react to the price signals and macroeconomic policy measures. It is revealed that in addition to export earnings, loans, investments, net sale of assets and international reserves the exchange rate could be another instrument to even out the imbalances. It is substantiated that the ability of the exchange rate to perform specified role in economy depends on the exchange rate regime (fixed or flexible), chosen by the country’s central bank. It is proved that automatic evening up of imbalances, reflected in BoP, is possible only under the conditions of flexible exchange rate regime. At the same time, sudden and excessive volatility of flexible exchange rates involves considerable risks for the real sector of economy in near-term outlook. It is detected that exchange rate and its regime in a particular country have considerable effect on the BoP and International Investment Position (IIP) figures. It is proved that first of all the exchange rate regime influences the volume of countries’ international reserves, monetary policy as well as all transmission mechanisms both in the aggregate of intersectoral relations within the national economy and interconnection of the country with the rest of the world.